Effectiveness of Zakat Distribution as a Sharia-Based Social Finance Instrument: Study BSI Scholarship Inspiration Program - Umami Hasibuan, Rima; Syahbudi, Muhammad; Syarvina, Wahyu (UIN Siber Syekh Nurjati Cirebon, 2025)
Poverty remains a significant barrier to economic development and access to higher education, particularly among underprivileged families. As a sharia-based social finance instrument, zakat has the potential to alleviate these barriers by supporting educational access through targeted programs. This study examines the effectiveness of zakat distribution managed by BSI Maslahat through its educational initiative, the BSI Scholarship Inspirasi program, aimed at underprivileged university students in North Sumatra. The research analyzes the program’s effectiveness using four key indicators: target accuracy, program socialization, goal achievement, and monitoring. Employing a qualitative approach combined with standard effectiveness measurement and Confirmatory Factor Analysis (CFA) via JASP software, the study uses purposive sampling to select student awardees as respondents. The results show that the overall implementation of the program is categorized as highly effective, with the highest achievement in the monitoring indicator (94%), followed by target accuracy (92%), goal achievement (91%), and program socialization (89%). These findings indicate that zakat distribution through the BSI Scholarship Inspirasi functions effectively as a sharia-compliant social finance tool and has a positive impact on its beneficiaries in higher education institutions across North Sumatra.Keywords: Scholarship; BSI Maslahat; BSI Scholarship Inspiration; Zakat Fund; Effectiveness